IDENTIFYING THE TECHNICAL PROBLEMS EXPERIENCED BY HIGH-SCHOOL AND UNDERGRADUATE STUDENTS IN PLAYING THE CELLO - Serpil UMUZDAŞ (Fırat University, 2019)
Technic in music instruments refers to the skills to use organs in order to produce required movements to play. Improvisation is possible through these skills. Therefore, acquiring these skills is important. This study aims at identifying the technical problems experienced by high-school and undergraduate students in playing the cello. The study employs quantative description method. The problems identified are interpreted through frequency and percentages based on experience and grade levels. The population of the study is the cello students attending 54 fine arts and sports high schools and 23 music education branches of the fine arts education faculties. The sample of the study includes eight randomly selected students from each institution. The data of the study were collected through a survey questionnaire. The items of the questionnaire were developed based on review of literature on right and left hand techniques in playing the cello. The questionnaire was reviewe by two specialists. After making necessary improvements on the questionnaire, it was administered to three cello students from high school and three cello undergraduates. Then it was administered to the sample. The findings of the study show that the majority of the participants have difficulty in using their left hands in playing the cello. In addition, they have difficulty in position shifting, agility, double stops, thumb position, grace notes, intonation and detache. The most of the participants also reported that they had not learnt the topics of sottie, martele and harmonics. It is expected that the findings of this study will guide the future studies on the topic.